EPIDEMIOLOGY, RISK FACTORS, DIAGNOSTICS AND PREVENTION OF DEEP VENOUS THROMBOSIS IN FRACTURES OF LONG BONES OF THE LOWER EXTREMITIES - O. NEMATZODA; S.KH. KURBANOV; D.SH. MAKHMUDOV (Паёми Сино, 2021)
A literature review presents a data concerning the incidence and risk factors for development of venous thromboembolic complications (VTEC), as well as their diagnosis and prevention in long bones fractures of the lower extremities (LBFLE). Literature data show that, despite the widespread implementation of preventive measures in case of LBFLE, it is not always possible to completely avoid VTEC. The main risk factors for their development are the injuries’ severity, the location and nature of the extremity bone fracture, the duration of immobilization, the amount of surgery performed for bone fragments stabilization, as well as age and the presence of concomitant diseases. In the diagnosis of thrombotic process, laboratory and radiation research methods play an essential role, and according to data they has varying degrees of sensitivity and specificity. However, to date, none of them has absolute diagnostic accuracy. Complex thrombosis prophylaxis significantly reduces the risk of VTEC development, however, the choice of the type and dosage of anticoagulants, as well as the duration of their use, remain controversial, and some authors recommend different approaches in this issue. In addition, the diagnostic criteria and therapeutic tactics for embologenic floating thrombi remain open for discussion. In this regard, the conduct of large randomized scientific studies aimed at early diagnosis, prevention and treatment of VTEC using modern diagnostic tests and new generation anticoagulants is relevant and allows to minimize the risk of disability and death.